The EGTC as a tool for cross-border multi-level governance - Medeiros, E. (2022)
Far from signalling the optimal organisational design and legislative framework for stimulating cross-border, transnational and interregional cooperation processes across Europe, the European Grouping of Territorial Cooperation (EGTC) affects various aspects of multi-level governance. In accepting this, this chapter discusses potential benefits of EGTCs as a tool to boost cross-border multi-level governance, based on the analysis of the EGTC implemented strategies. This chapter proposes a novel conceptual framework to classify cross-border EGTCs based on their contribution to reducing border barriers and increasing the: (i) strategic, (ii) intermediary and (iii) rogue type of territorial capital of the cross-border region. It concludes that only a few ongoing EGTCs have been effective enough to respond to the main territorial development issues faced by the cross-border regions they cover. In this context, the author suggests a strategic makeover of several EGTCs with a view to concentrating on specific, rather than generic, strategic policy goals. In particular, several EGTCs’ strategic foci should shift to reducing border barriers and promoting cross-border or transnational spatial planning.